Managerial Ownership, Leverage, Profitability, Corporate Value: An Interactive Effect In Indonesia Stock Exchange - Mappadang, Agoestina (Lembaga Penelitian dan Pengabdian kepada Masyarakat UPJ, 2021)
Managerial ownership, firm value and financial characteristic have long been critical issue with regards to company’s financial decision making. If the profitability higher and more assignable profit there and it is the higher value of the firm. Purpose of this study to analyze how the impact of Managerial Ownership, Leverage, Profitability on the firm value. The population take from companies listed in Indonesian Stock Exchange 2015 - 2019. The population taking from property, real estate and building construction. This research method using for this study is a purposive sampling with multiple of regression analysis. The result of this research are managerial ownership affects the value of the firm, leverage does not affect the value of the firm and profitability affects on value of the firm. The simultaneous of managerial ownership, leverage and profitability have no significant on firm value. This study’s Implication will support for stakeholder theory that management as an agent must develop a relationship with stakeholders by embarking on environmental friendly practice to maintain a positive value. Besides, value of the company has created must be prioritized to help the companies enhance their competitive advantage to strengthen on financial performance.